Reconstruction of Complex Soft Tissue Defects of the Heel With Versatile Double Skin Paddle Anterolateral Thigh Perforator Flaps: An Innovative Way to Restore Heel Shape - He, Jiqiang; Guliyeva, Gunel; Wu, Panfeng; Yu, Fang; Qing, Liming; Tang, Juyu (Frontiers in Surgery, 2022)
Background: Complex heel defects constitute a significant challenge for plastic surgeons. Objectives: In this study, the versatilities of the free double skin paddle ALT flap in the reconstruction of complex soft-tissue defects of the heel were explored. Methods: From January 2010 to December 2019, 16 patients (13 male and 3 female) aged 16–74 years underwent double skin paddle ALT flap reconstruction in our department. All patients had large defects located at the heel, with 5 patients having dead space. Underlying structures such as vessels, bones, and tendons were exposed in all cases. Results: Flap survival rate was 100% after the reconstruction. 11 double skin paddle ALT flaps and 5 vastus lateralis muscle-chimeric double skin paddle ALT flaps were used. The size of the skin flap ranged from 9.5 × 4.5 cm2 to 22 × 10 cm2, and the muscle segment's size ranged from 6 × 3 × 1 cm3 to 10 × 3 × 2 cm3. The mean follow-up was 22.6 months (range, 10–81 months). The wounds healed well, providing reliable soft tissue coverage and good heel contour. All patients ambulated independently during the follow-up period. Most patients regained protective sensation. The average two-point discrimination was 32.7 mm (range, 27–37 mm). Conclusion: The double skin paddle ALT flap is a feasible option for the reconstruction of complex heel defects with good functional and aesthetic results. Nonetheless, further studies comparing the double skin paddle ALT flap to other flap techniques are needed.